A Marginal Contribution Theory-Based Energy Efficiency Contribution Analysis for Integrated Energy System - Yang, Shihai; Chen, Mingming; Zuo, Qiang (Frontiers in Energy Research, 2021)
The energy efficiency analysis is a prerequisite for the construction of the integrated energy system (IES). In this paper, a novel energy efficiency analysis method is proposed considering different energy subsystems in the IES. First, the energy efficiency index of the subsystems and conversion devices is formed for elaborating their influence on the IES. The IES is composed of four energy subsystems, i.e. power/gas/heat/cooling subsystem, and six energy conversion devices. Next, the energy efficiency contribution models of energy subsystems and conversion devices are proposed based on their energy efficiency index respectively. Then, in order to calculate the energy flow in the IES, an equivalent topological model of the IES names weighted directed graph is proposed to calculate the energy efficiency contribution. Finally, an actual park is employed to illustrate the validity of the proposed analysis method.